The comparative effects of oral Chinese patent medicines combined with western medicine in stable angina: A systematic review and network meta-analysis of 179 trials - Huang, Peiying; Li, Zhishang; Chen, Li; Zeng, Jing; Zhao, Shuai; Tang, Yong; Huang, Bixuan; Guan, Hansu; Chen, Yan; Feng, Yuchao; Lei, Sisi; Wu, Qihua; et al. (Frontiers in Pharmacology, 2022)
Background: Stable angina is a common condition with high morbidity and mortality rates. It has been reported that combining oral Chinese patent medicines (OCPMs) and Western medicine (WM) could potentially achieve a better effect than WM alone. However, the optimal OCPMs for stable angina remain controversial. Methods: PubMed, Embase, Web of Science, Cochrane Library, Ovid-Medline, Clinical Trials.gov, China National Knowledge Infrastructure, Wanfang Database, Weipu Journal Database, and Chinese Biomedical Literature Database were all searched from inception to March 13, 2022. We employed Version 2 of the Cochrane risk-of-bias tool (ROB2) to assess the overall quality of the selected studies. We also used R 4.1.2 and STATA 14.0 software applications to perform network meta-analysis, followed by sensitivity and subgroup analysis. Results: A total of 179 randomized controlled trials with 16,789 patients were included. The selected trials were all assessed as some concerns. OCPMs combined with WM had a better treatment effect than WM alone. In terms of the effective clinical rate, a significant increase was detected for Qishen Yiqi dripping pill (QSYQ)+WM as compared with Shensong Yangxin capsule (SSYX)+WM, Shexiang Baoxin pill (SXBX)+WM, Tongxinluo capsule (TXL)+WM, Xuefu Zhuyu capsule (XFZY)+WM, Qiliqiangxin capsule (QLQX)+WM, Naoxintong capsule (NXT)+WM, Fufang Danshen dripping pill (FFDS)+WM, and Danlou tablet (DL)+WM. QSYQ+WM had the highest-ranking probability (98.12%). Regarding the effective rate in ECG, QSYQ+WM was superior to SXBX+WM, TXL+WM, DL+WM, FFDS+WM, and NXT+WM. QSYQ+WM ranked first (94.21%). Respecting weekly frequency of angina, QLQX+WM obtained a better effect than FFDS+WM, Kuanxiong aerosol (KXQW)+WM, NXT+WM, QLQX+WM, SSYX+WM, SXBX+WM, and TXL+WM. QLQX+WM ranked first (100.00%). Regarding the duration of an angina attack, KXQW+WM was superior to SSYX+WM; KXQW+WM ranked first (95.71%). Adverting to weekly nitroglycerin usage, TXL+WM had the highest-ranking probability (82.12%). Referring to cardiovascular events rate, DL+WM had the highest effect (73.94%). Additionally, SSYX+WM had the lowest rate of adverse drug reactions (1.14%). Conclusions: OCPMs combined with WM had a higher efficacy. QSYQ+WM, QLQX+WM, KXQW+WM, TXL+WM, DL+WM, SSYX+WM, and SXBX+WM merit further investigation. SXBX+WM is presumably the optimal treatment prescription for both clinically-effective and cardiovascular event rates. Further high-quality empirical research is needed to confirm the current results.